2.6k views
0 votes
Simplify the following exponential expression. Show your work step by step and list the Properties of Exponents used to solve this problem next to your work.

Simplify the following exponential expression. Show your work step by step and list-example-1
User Fav
by
4.9k points

1 Answer

2 votes

Solution:


(3x^0(2x^3y^2)^4)/((4x^7y^4)^2)


(3x^0(2x^3y^2)^4)/((4x^7y^4)^2) =(3(1)(2x^3y^2)^4)/((4x^7y^4)^2) Since,
a^0=1


(3x^0(2x^3y^2)^4)/((4x^7y^4)^2) =(3(2)^4(x^3)^4(y^2)^4)/((4)^2(x^7)^2(y^4)^2) Since,
(ab)^m=a^mb^m


(3x^0(2x^3y^2)^4)/((4x^7y^4)^2) =(3(16)x^(12)y^(8))/(16x^(14)y^(8)) Since,
(a^m)^n=a^(mn)


(3x^0(2x^3y^2)^4)/((4x^7y^4)^2) =(3x^(12)y^(8))/(x^(14)y^(8))


(3x^0(2x^3y^2)^4)/((4x^7y^4)^2) =3x^(12-14)y^(8-8) Since,
(a^m)/(a^n) =a^(m-n), a^0=1


(3x^0(2x^3y^2)^4)/((4x^7y^4)^2) =3x^(-2)y^(0)


(3x^0(2x^3y^2)^4)/((4x^7y^4)^2) =(3)/(x^2)


User Qed
by
4.9k points